Multidimensional thermochemical cycles – Exploring three dimensions: Designer tool for estimation of the thermodynamics of reactions under varying conditions and for estimating elusive thermodynamic data - Glasser, Leslie; Roobottom, H.; Jenkins, H.D. (Academic Press, 2014)
Born–Haber–Fajans (BHF) thermochemical cycles describe links among different aspects of a chemical reaction at a common temperature and pressure, independent of the actual process of the reaction, and so provide methods for evaluation of otherwise missing information. We show that the standard two-dimensional BHF cycle can be extended to allow for consideration of temperature and pressure variation, using temperature changes for the reaction between HCl and Na as our illustrative example. Such extension provides possibilities of multiple interrelationships among contemplated states of the process of the reaction, so enhancing the related thermodynamic information. Although thermodynamics and kinetics do not necessarily coincide, it may be possible, utilizing such insights, to circumvent kinetically-disallowed steps in a chemical synthesis by choosing an alternative but thermodynamically favored route.